2018
DOI: 10.1016/j.mce.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the FTO gene inhibits insulin secretion: An in vitro study using GRINCH cells

Abstract: Expression of fat mass and obesity-associated gene (FTO) and ADP-ribosylation factor-like 15 (ARL15) in human islets is inversely correlated with HbA. However, their impact on insulin secretion is still ambiguous. Here in, we investigated the role of FTO and ARL15 using GRINCH (Glucose-Responsive Insulin-secreting C-peptide-modified Human proinsulin) clonal rat β-cells. GRINCH cells have inserted GFP into the human C-peptide insulin gene. Hence, secreted CpepGFP served to monitor insulin secretion. mRNA silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
(64 reference statements)
1
22
0
Order By: Relevance
“…Methylation level play a very important role in gene expression [33]. Two previous studies found that FTO expression level was associated with insulin secretion, which may lead T2DM [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Methylation level play a very important role in gene expression [33]. Two previous studies found that FTO expression level was associated with insulin secretion, which may lead T2DM [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Since the levels of preproinsulin mRNA in the islets of individuals with normoglycaemia or type 2 diabetes do not significantly differ, its stability is unlikely to be affected in type 2 diabetes [32,33]. On the other hand, in mouse islets and insulinoma (MIN6) cells exposed to proinflammatory cytokines, no-go and nonsense-mediated RNA decay pathways are upregulated, lowering the levels of preproinsulin mRNA [34].…”
Section: Regulation Of Preproinsulin Mrna Stability In Health and Diamentioning
confidence: 99%
“…Whole body knockouts and nervous system specific knockouts of Fto in mice result in postnatal growth deficiencies (Gao et al, 2010), however, its specific function in β cells is debated. In T2D human islets, FTO expression is reduced (Kirkpatrick et al, 2010;Taneera et al, 2018) and the FTO gene has decreased DNA methylation (Dayeh et al, 2014). Several groups have investigated the functional role of FTO in pancreatic islets using different experimental models.…”
Section: M6a Rna Methylationmentioning
confidence: 99%
“…Overexpression of FTO in rat INS-1 cells appeared to affect first wave insulin secretion (Russell and Morgan, 2011), whereas overexpression in mouse MIN6 cells resulted in the inhibition of GSIS without changes in insulin gene expression (Fan et al, 2015). Given the discrepant results of these studies, in addition to the caveats associated with overexpression studies, perhaps the more relevant functional assessment was the use of siRNA knockdown to deplete FTO in an engineered human insulin secretion reporter rat β cell line (GRINCH) (Taneera et al, 2018). In these experiments, depletion of FTO resulted in decreased insulin mRNA expression and insulin secretion (Taneera et al, 2018).…”
Section: M6a Rna Methylationmentioning
confidence: 99%
See 1 more Smart Citation